(untitled) (Journal of Oriental Studies, 2023)
In a globalized world with developing technologies and economies, the industrial revolution has shaped countries’ economic, social and demographic development processes. While total population figures are increasing led by Asian countries Eastern Asian ones are experiencing a demographic downfall. South Korea attracts attention with having one of the lowest birth rates in the world and changing labor market conditions which cause labor shortages in certain sectors. Despite all the efforts of different governments none of them manages to reverse the negative demographic trend of the country. The purpose of this paper is to analyze demographic indicators and identify the root causes of the negative demographic trends that become current bottlenecks for South Korea. With a combination of using historical data on demographic trends, analysis of government initiatives and the current situation, this paper points outnumber factors that slow down the effectiveness of government initiatives and provides alternative solutions which are proven to be effective in different country experiences to reverse the demographic trends in the country.